Spectroscopic analysis of amyloid fibril formation in SH3‒domains. Issue 4 (2003) - Ventura Ventura, Salvador Salvador; Serrano Serrano, Luis Luis
Abstract : The aggregation of proteins in fibrillar form is a problem of critical importance in a wide range of abnormal disease states. To decipher the molecular mechanism of formation of protein fibrillar aggregates we have chosen to study as model SH3 domains that exhibit different abilities to polymerize into amyloid fibrils. While being not related to any known disease, the SH3 domain of the p85α subunit of phosphatidylinositol 3 kinase has been found to form amyloid fibrils in vitro under acidic conditions, meanwhile, we have found that the spectrin SH3‒domain, sharing the same fold and some sequential identity keeps its native conformation under the same conditions. The use of spectroscopic methods to study these properties is illustrated in the present job, and correlated to direct sample observation by electron microscopy.